Determination of physiochemical properties of Gum Arabic as a suitable binder in emulsion house paint - Yaumi, Ali L.; Murtala, Ahmed M.; Muhd, Habiba D.; Saleh, Fatima M. (International Journal of Environment, 2016)
Gum Arabic “GA” is an organic adhesive produced from a tree called named Acacia Senegal. The gum has a wide range of industrial uses, especially in areas of feeds, textiles, and pharmaceuticals. It is used as emulsifier and serves mostly as stabilizer in both cosmetic and food products which contains oil water interface. GA sample was collected, formulated and prepared into various concentrations ranging from 20%w/v to 85%w/v. The quality and applicability of well characterized materials are directly related to their physical and chemical properties. From the physiochemical analysis, the result revealed that all the samples were slightly acidic (pH ranging from 4.81-6.41). This range is in good agreement with reported pH values for gum arabic and other Acacia gums by several authors. . The binding strength increases as the number of days increases for example in sample F (50%w/v) gum Arabic concentration increases from 1.5 in the 1st day to 1.97 in the 28th day. The samples prepared are denser than water which indicates that the density increases as the percentage concentration of the samples increases and the relative density of the gum solution is independent on time. The binding strength of sample G (75%w/v) gum concentration compared well to that of polyvinyl acetate (PVA). International Journal of Environment Vol. 5 (1) 2016,  pp: 67-78